1991
DOI: 10.1080/0028825x.1991.10415497
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the frost hardiness ofPodocarpus totara

Abstract: The late-winter frost hardiness of seedlings of eight provenances of totara (Podocarpus totara G.Benn. ex I)on) raised in a common environment was tested in a corarolled environment frost room. Frost damage was assessed visually. Frost hardiness temperatures of file provenances ranged from-5~ to-10~ A significant increase in frost damage occtared at lower temperattaes, and the frost hardiness of the wovenances was positively couelated with their altitude of origin. The possibility of allele frequency-depmdent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…ex Don.) (Hawkins et al, 1991). Similar patterns have been described for Mexican coniferous populations distributed along the altitudinal gradients, such as Pinus devoniana Lindl.…”
supporting
confidence: 50%
“…ex Don.) (Hawkins et al, 1991). Similar patterns have been described for Mexican coniferous populations distributed along the altitudinal gradients, such as Pinus devoniana Lindl.…”
supporting
confidence: 50%
“…Hawkins et al (1991) using the same seedlots found that frost hardiness of P. totara was positively correlated with altitude of seed origin for a limited selection of central to southern region North Island provenances, ranging from 30-540 m a.s.l. in altitude.…”
Section: Discussionmentioning
confidence: 96%
“…(Bannister & Lee 1989), Leptospermum scoparium Harris & Decourtye 1991), and Podocarpus totara (Hawkins et al 1991). For example, differences in maximum summer frost hardiness temperatures of Nothofagus were small between populations from different altitudes, but in mid winter hardiness temperatures were -11.5°C for high altitude populations and only -4.5°C for low altitude populations (Greer et al 1989).…”
Section: Resultsmentioning
confidence: 99%